Co3O4 Nanosheets as Active Material for Hybrid Zn Batteries - Tan, P.; Chen, B.; Xu, H.; Cai, W.; He, W.; Liu, M.; Shao, Zongping; Ni, M. (Wiley, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. The rapid development of electric vehicles and modern personal electronic devices is severely hindered by the limited energy and power density of the existing power sources. Here a novel hybrid Zn battery is reported which is composed of a nanostructured transition metal oxide-based positive electrode (i.e., Co 3 O 4 nanosheets grown on carbon cloth) and a Zn foil negative electrode in an aqueous alkaline electrolyte. The hybrid battery configuration successfully combines the unique advantages of a Zn–Co 3 O 4 battery and a Zn–air battery, achieving a high voltage of 1.85 V in the Zn–Co 3 O 4 battery region and a high capacity of 792 mAh g Zn -1 . In addition, the battery shows high stability while maintaining high energy efficiency (higher than 70%) for over 200 cycles and high rate capabilities. Furthermore, the high flexibility of the carbon cloth substrate allows the construction of a flexible battery with a gel electrolyte, demonstrating not only good rechargeability and stability, but also reasonable mechanical deformation without noticeable degradation in performance. This work also provides an inspiring example for further explorations of high-performance hybrid and flexible battery systems.